ASAS ULTIMUM REMEDIUM DALAM PENERAPAN SANKSI PIDANA TERHADAP TINDAK PIDANA PERPAJAKAN OLEH WAJIB PAJAK - Sarah Hasibuan; Madiasa Ablisar; Marlina Marlina; Utari Maharany Barus (Universitas Sumatera Utara, 2015)
ABSTRACT Legal settlement of tax crime specified in section 44B of Act Number 28 of 2007 on the third amendment to the Law No. 6 of 1983 on General Provisions and Tax Procedures (UUKUP) is the grant of authority by law to the Minister of Finance by reason of the interest of the state revenue, requesting the Attorney General to stop the tax crime investigation process. KUP Law Article 44B shows that the actual application of the criminal law violations are not to be Primum remedium, but more oriented to remedium ultimum. This is stated explicitly, although the infringement lawsuit by the taxpayer has been declared complete, but the Minister of Finance can still ask the Attorney General to stop the investigation due consideration to the interests of state revenue, if it has not been declared complete means the Minister of Finance can be directly ruled Directorate General of Tax to stop it. Keywords: Ultimum Remedium, Tax Crime.